Colloidal Centrifugation of Stallion Semen Results in a Reduced Rate of Sperm DNA Fragmentation. Issue 2 (7th July 2012) - Crespo, F; Gosalvez, J; Gutiérrez‐Cepeda, L; Serres, C; Johnston, SD
Contents: Stallion spermatozoa recovered and examined immediately after colloidal centrifugation resulted in a higher straight‐line velocity (VSL) than sperm processed using direct conventional centrifugation (p = 0.000), but there was no differences in the progressive motility or sperm DNA fragmentation (SDF) as determined by the sperm chromatin dispersion assay. However, when centrifuged spermatozoa were incubated at 37°C for 24 h to determine the rate of SDF (r‐SDF), a lower r‐SDF (p = 0.0011) was observed in those sperm recovered after colloidal separation (0.5 ± 0.1%/h) compared to direct (1.2 ± 0.4%/h) or no centrifugation (r‐SDF = 1.2 ± 0.3%/h). These results confirm that colloidal separation of stallion spermatozoa results in prolonged sperm DNA longevity, but these differences were only apparent following a period of incubation and dynamic assessment. Consequently, we strongly recommend the use of the dynamic form of the SDF assay for evaluating centrifugation and/or other ex vivo procedures, as a single basal assessment of SDF may inadvertently result in a false‐positive evaluation of DNA quality.